DEVELOPMENT OF SOCIO SCIE NTIFIC ISSUE– PBL MODULE FOR GLOBAL WARMING TOPIES IN SCIENCE LEARNING - citra wulansari; rani oktavia (Universe, 2022)
Science learning in the 2013 curriculum seeks to solve real-life problems and understand the impact of science learning on technological developments, life and its impact in the future so that learning becomes more meaningful. However, students require to be trained to get the ability to solve problems scientifically through scientific and social issues. The observations result in the field reveal that there are limited materials of teaching that can train students' problem-solving skills. To overcome these problems, materials are needed, namely a module of science based on Socio Scientific Issues by applied the model of Problem Based Learning. The research purpose is to generate a Socio Scientific Issue-based science module with a Problem Based Learning model of valid and practical global warming material. The research type by used is research and development or Research and Development (R&D). The model of development used is a 4-D model (four-D models) with three modification stages consisting of define, design, and develop. This module is validated by 3 validators. The research instrument used was a validity and practicality questionnaire. The validity result of test obtained a validity value of 85.17% with a category is very valid. The practicality result of test by the teacher obtained a score of 87.65% in the category is very practical and the practicality result of test by the students obtained 89.95% in the category is very practical. Based on these results, it is concluded that the Socio Scientific Issue-based science module with a Problem Based Learning model of global warming material for seventh grade junior high school students is valid and practical.